Study of clinical and nerve conduction study correlation in patients of diabetic neuropathy in diabetes mellitus type 2 - Patil, Manish; Dhruw, Avon Kumar; Gupta, Shashank (International Journal of Advances in Medicine, 2018)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia with disturbance of carbohydrate, fat, and protein metabolism resulting from defects in insulin secretion, insulin action or both with an increased risk of neuropathy. Early diagnosis and management of diabetic polyneuropathy (DPN) are crucial as failure to diagnose can lead to serious consequences, including disability and amputation. Present study aimed at investigating the demographic profile and correlation of clinical features with nerve conduction studies in patients with diabetic neuropathy in type 2 diabetes mellitus. Methods: The cross-sectional study design with total 66 patients of type 2 DM were selected in 30 to 60-year age groups, from Pt. Jawaharlal Nehru Memorial Medical College, Department of Medicine, Raipur (C.G.) (Pt. JNMMC) and associated hospital. Descriptive statistics and χ2 test were used for analysing the data. Results: Total 66 patients were selected, Most of the patients are presenting with tingling sensation (n=64, 97.0%) and burning feet (n=52, 78.8%), NCV is mostly absent in the tibial nerve (n=52, 78%), sural nerve (n=63, 95.5%) and planter nerve (n=41, 62.1%) while it is largely normal in median nerve (n=54, 81.8%) and ulner nerve (n=61, 92.4%). Tingling sensation, burning feet, diminished vibration sensation and diminished light touch are significantly associated (p=0.00) with NCV in different nerves. Conclusions: Limitations of study includes small sample size, lack of general population, and a control group. Diabetes mellitus is a chronic illness with an increased risk of neuropathy. NCS having high sensitivity and specificity for detection of DPN. Understanding the NCS and its correlates in patients with DPN is crucial for early detection and development of effective management and strategies to prevent its complications.